Pengaruh Kualitas Produk, Promosi Media Sosial, dan Lokasi terhadap Keputusan Pembelian Konsumen di Toko Aulia Lebaksiu Tegal - Nur Atiq Fitriyani (Jurnal Manajemen Bisnis Digital Terkini, 2025)
This study aims to analyze the influence of product quality, social media promotion, and location on consumer purchasing decisions at Toko Aulia Lebaksiu Tegal. The research background stems from the growing retail competition that requires business owners to thoroughly understand consumer behavior. The research employs a quantitative approach with a causal research design. The sample consists of 100 respondents who are consumers of Toko Aulia, selected using purposive sampling techniques. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression analysis. The findings indicate that all three independent variables—product quality, social media promotion, and location—have a positive and significant effect on consumer purchasing decisions. The coefficient of determination (R²) value of 0.68 reveals that 68% of the variation in purchasing decisions can be explained by these three variables, while the remaining 32% is influenced by other factors outside the model. Partially, social media promotion has the most dominant influence among the variables. These results highlight that improving product quality, utilizing social media effectively, and choosing a strategic location are key factors in developing marketing strategies that enhance consumer purchasing decisions in the local retail sector.